2019
DOI: 10.1186/s12884-019-2616-9
|View full text |Cite
|
Sign up to set email alerts
|

Process evaluation of the community-based newborn care program implementation in Geze Gofa district, south Ethiopia: a case study evaluation design

Abstract: BackgroundThe Community-Based Newborn Care (CBNC) program is a comprehensive strategy designed to improve the health of newborns during pregnancy, childbirth, and the postnatal period through health extension workers at community levels, although the implementation has not been evaluated yet. Therefore, this study aimed to evaluate the process of the CBNC program implementation in Geze Gofa district, south Ethiopia.MethodsA case study evaluation design with a mixed method was employed from May 1 to 31, 2017. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(53 citation statements)
references
References 25 publications
0
53
0
Order By: Relevance
“…However, the CBNC programme training was considered to be of low intensity by health centre staff and district health managers. Indeed there is some evidence that HEWs were not treating young infants with possible severe bacterial infection according to national guidelines [ 21 ]. Further, studies have shown that training alone has little effect in improving health care provider performance [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the CBNC programme training was considered to be of low intensity by health centre staff and district health managers. Indeed there is some evidence that HEWs were not treating young infants with possible severe bacterial infection according to national guidelines [ 21 ]. Further, studies have shown that training alone has little effect in improving health care provider performance [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The program also utilizes health developmental armies [HDA] and other existing effective community mobilization mechanisms to scale up the service and to improve maternal and newborn care practices and careseeking [13]. There is also evidence that showed community-based service utilization is being provided for newborn PSBI management [12,19,20]. But, the study findings also showed that there were newborns that did not get treatment service besides the presence of signs or symptoms suggestive to PSBI [12,19].…”
Section: Introductionmentioning
confidence: 99%
“…This evaluation assessed the implementation status of CEmONC program, using availability, compliance and acceptability dimensions based on the interests of stakeholders. Availability is the sub-dimensions to measure access to health care in relation with the volume and types of services, and adequacy of resources (physical and human) used to provide CEmONC services [17]. Compliance is the degree to which CEmONC services is being implemented in UoGCSH by health care providers complies with the national standards and clinical protocols [17].…”
Section: Evaluation Approach and Dimensionsmentioning
confidence: 99%
“…Availability is the sub-dimensions to measure access to health care in relation with the volume and types of services, and adequacy of resources (physical and human) used to provide CEmONC services [17]. Compliance is the degree to which CEmONC services is being implemented in UoGCSH by health care providers complies with the national standards and clinical protocols [17]. Acceptability determines the level of care givers perceptions of care received from CEmONC services by health care providers [17].…”
Section: Evaluation Approach and Dimensionsmentioning
confidence: 99%